(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
A comparative analysis of the structural organization of lymph nodes of different localization with an assessment of the effect of pre-eclampsia was performed. The lymph nodes of different localizations were studied in two groups of deceased women who died during pregnancy: there were the control group or the comparison group – where deceased women from other diseases were examined in comparison to those who died from preeclampsia. It was noted that the morphometric indicators of the morpho functional zones of the lymph nodes of all localizations underwent changes in pre-eclampsia. In paratracheal lymph nodes, the area of lymphoid follicles, paracortex, and soft tissues were expanded and the occupied area of other zones was decreased. In the mesenteric and subhepatic lymph nodes, a more significant increase in the area of lymphoid follicles and pulp cords was noted. A significant expansion of the area of paracortex was noted in the sub splenic lymph nodes and was almost twice as much as the control of the same group. In these lymph nodes, there was also a significant decrease in the area of cortex area and sinuses of the medullary layer